A novel lateral flow assay based on GoldMag nanoparticles and its clinical applications for genotyping of MTHFR C677T polymorphisms. Issue 6 (25th January 2016) - Hui, Wenli; Zhang, Sinong; Zhang, Chao; Wan, Yinsheng; Zhu, Juanli; Zhao, Gang; Wu, Songdi; Xi, Dujuan; Zhang, Qinlu; Li, Ningning; Cui, Yali
Abstract : A visual genotyping method combining ARMS-PCR with GoldMag-based lateral flow assay. Abstract : Current techniques for single nucleotide polymorphism (SNP) detection require tedious experimental procedures and expensive and sophisticated instruments. In this study, a visual genotyping method has been successfully established via combining ARMS-PCR with gold magnetic nanoparticle (GoldMag)-based lateral flow assay (LFA) and applied to the genotyping of methylenetetrahydrofolate reductase ( MTHFR ) C677T. C677T substitution of the gene MTHFR leads to an increased risk of diseases. The genotyping result is easily achievable by visual observation within 5 minutes after loading of the PCR products onto the LFA device. The system is able to accurately assess a broad detection range of initial starting genomic DNA amounts from 5 ng to 1200 ng per test sample. The limit of detection reaches 5 ng. Furthermore, our PCR-LFA system was applied to clinical trials for screening 1721 individuals for the C677T genotypes. The concordance rate of the genotyping results detected by PCR-LFA was up to 99.6% when compared with the sequencing results. Collectively, our PCR-LFA has been proven to be rapid, accurate, sensitive, and inexpensive. This new method is highly applicable for C677T SNP screening in laboratories and clinical practices. More promisingly, it could also be extended to the detection of SNPs of other genes.